Accelerated Ageing Tests of Clay Roofing Tiles under Salt Mist Atmosphere - Cruz, C. (2011)
Clay roof tiles are largely used in traditional construction in Portugal and other countries. Due to the exposition to a salt mist atmosphere, some cases of accelerated decay have been affecting the ceramic roofing tiles durability in coastal zones. This paper presents two types of accelerated weathering tests of clay roofing tiles in a climatic chamber. In both of these tests the specimens are subjected to an atmosphere of salt mist produced by a NaCl solution spray. The first is a simple cyclic test with each cycle consisting of a salt mist period and a drying period. The second is a composite test consisting of several phases. Each phase consists of several simple cycles followed by a large drying period. In each phase the specimens are subjected to cleaning and wetting operations. The results obtained were discussed and compared. Accelerated ageing tests can cause different levels of alteration and degradation of the same types seen in natural exposed ceramic tiles. The composite test induced more degradation on the specimens than the simple cyclic test. Hydrophobic surface tiles may resist longer to salty mist but they can suffer higher damage than non-hydrophobic tiles. Some parameters as the raw materials and the firing temperature can influence the behaviour of the tiles under salt mist. Characteristics as the water absorption under vacuum and the porous structure may give some information about the relative durability of different types of tiles.